Where is home? Changing conceptions of the homeland in the Surinamese-Javanese diaspora - Hoefte, Rosemarijn; Mingoen, Hariëtte (Wacana, Journal of the Humanities of Indonesia, 2022)
In 1890 the first Javanese indentured labourers arrived in Suriname to work on the colony’s plantations. In total almost 30,000 indentured and free immigrants arrived in this small Caribbean colony. Fifty years later, at the end of the migration period, they formed more than one fifth of the population. Consequently, they constituted a substantial community which had to adapt to a different socio-cultural environment but, at the same time, managed to keep in touch with their homeland. The Javanese thus shaped their own cultural expressions and traditions in Suriname. We attempt to analyse the processes of identity formation, adaptation, and re-creation of culture by examining the worlds which the migrants created by looking at four distinct time periods. The first two (1930s and 1950s) focus on the Surinamese-Javanese population’s connections with Suriname and Indonesia, the latter two (1970s and the present century) on Suriname and the Netherlands. The migration of Javanese from Suriname to the Netherlands around Suriname’s independence in 1975 has in effect produced a third homeland. In terms of identity, the Surinamese Javanese themselves now identify strongly with Suriname as they proudly point out “Ik ben een Javaan uit Suriname” (I am a Javanese from Suriname).